Functional Outcome of Surgical Management of Trimalleolar Fractures - Rizwan Anwar, Omer Farooq Tanveer, Tanveer Haider, Muhammad Abdul Hannan, Muneeb Ur Rehman Cheema, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Trimalleolar fracture is very hamstring if it not maintained accurately. It is one of the pitiful condition. Trimalleolar ankle injuries have become more common in the last decade, with up to 40 per 100,000 people affected each year. Study design: It is a prospective study conducted for the duration of six months from February 2022 to July 2022 at Islam teaching hospital, Sialkot. Material and Methods: The study was carried out on 52 patients who were admitted in tertiary care unit during a period of one year. All the patients were following inclusion criteria, those who were unable to fulfill were excluded from the study. There were 36 males and 16 females taken for study. 30 patients had injury in the right side and 18 reported left side injury. The hospital review board committee give the approval to the study. The data was collected and statistically analyzed by using the renowned software SPSS. The result were presented in the form of table. Results: The injury pattern that was frequently observed in patients was supination external rotation reported in 40 patients. While 8 had pronation external rotation and 4 had to face supination adduction pattern. There were 4 cases that complaint about superficial infection and deep infection was observed in case of 2 patients. Conclusion: It is concluded that for the fixation of Trimalleolar fractures, there is a need for proper planning and reduction of lateral malleolus fractures by a lateral plating method. Keywords: ankle fracture, operative planning and Posterior malleolus fracture.